Produksi dan Kualitas Rumput Brachiaria humidicola (Rend.) Sch, Digitaria decumbens Stent dan Stenotaphrum secundatum (Walter) O.Kunt. di Bawah Naungan Sengon, Karet dan Kelapa Sawit - W Kurniawan; L Abdullah; M A Setiana (Media Peternakan, 2007)
The experiment was conducted to investigate the adaptive grasses growing under shading albizia, rubber and oil palm canopy. Three species of tropical grasses (Brachiaria humidicola (Rend.) Sch., Digitaria decumbens Stent, dan Stenotaphrum secundatum (Walter) O.Kunt. were cultivated for at least four months. The parameters of research were productivity (including tillering rate) and nutrient quality of each grass. Data were analyzed using Split-plot design and for the significant differences were further tested by Least Significant Different (LSD). The result showed that B. humidicola production was better than other species in plantation and forest shaded. This species producting higher fresh yield and crude protein, but its tillering rate was poor. S. secundatum, although its production was not as great as B. humidicola, this grass had the greatest tillering rates compared to the others. It can be recommended that S. secundatum is persistent species, and has a good productivity for a long periode of time under shading. Key words: tropical grasses, shading, tillering rates, persistent